Vascular Complications after Facial Filler Injection: A Literature Review and Meta-analysis - Sito, Giuseppe (J Clin Aesthet Dermatol, 2019)
Background: Vascular occlusion during the injection of facial fillers is uncommon, but can result in serious adverse events, including necrosis, blindness, and stroke. Objectives: We explored factors that influence the frequency and severity of vascular complications during filler injections. Methods: This was a meta-analysis that included case reports and case series published during the years 2004 to 2016 describing patients who experienced any type of vascular complication after an aesthetic procedure. In addition to the descriptive analysis of the variables retrieved, a logistic regression for predicting the outcome of the vascular event was performed. Results: The analysis included 93 cases described in 30 articles. Blindness was the main consequence of the vascular complications (n=57; 61%). The reported outcome was partial or total recovery in 24 cases (28%) and no improvement in 61 cases (72%). Hyaluronic acid (HA) and autologous fat were the two fillers most frequently involved in vascular occlusions, with autologous fat showing a stronger trend toward no improvement than HA. Involvement of the ophthalmic and retinal arteries was most frequently associated with no improvement. Conclusion: Injury to ophthalmic and retinal arteries during the injection of facial fillers can result in irreversible serious adverse events. Physicians performing facial filler injections should have a proficient knowledge of anatomy.